Roberts uterus: a rare congenital anomaly - Sardeshpande, Nagendra; Chipalkatti, Pratima; Doctor, Jainesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A 23-year-old girl presented with severe cyclical lower abdominal pain during menstruation since menarche, which had increased since the last 4 years. Transabdominal ultrasound showed adnexal mass with no internal vascularity; MRI reported it as bicornuate uterus with one non-communicating right uterine horn with haematometra. On hysteroscopy there was evidence of septate uterus communicating only to the left ostia. Ultrasonography-guided hysteroscopic resection of septa with drainage of haematometra was done. Patient is presently asymptomatic.